Shortening of subjective visual intervals followed by repetitive stimulation. - Fuminori Ono (Public Library of Science (PLoS), 2011)
Our previous research demonstrated that repetitive tone stimulation shortened the perceived duration of the preceding auditory time interval. In this study, we examined whether repetitive visual stimulation influences the perception of preceding visual time intervals. Results showed that a time interval followed by a high-frequency visual flicker was perceived as shorter than that followed by a low-frequency visual flicker. The perceived duration decreased as the frequency of the visual flicker increased. The visual flicker presented in one hemifield shortened the apparent time interval in the other hemifield. A final experiment showed that repetitive tone stimulation also shortened the perceived duration of preceding visual time intervals. We concluded that visual flicker shortened the perceived duration of preceding visual time intervals in the same way as repetitive auditory stimulation shortened the subjective duration of preceding tones.